Análisis del discurso político en medios de comunicación. - Villavicencio Guerrero, Felipe (2016)
This academic article is a serie of reflections about the analysis of political discourse in the context of social media: How is it transmitted and projected through mechanisms of mass reproduction? It is also an academic and analytical exploration of the most significant theoretical contributions that operate around the study of the analysis of political discourse and its effects on society. It also includes the presentation of a methodology (indicative) from a quantitative and qualitative source of analysis of political discourse that has resulted from the work experience in this particular dimension of discourse, the main reason for this methodology is to provide institutions and social groups of instruments of synthesis and discursive media that may require of detailed and systematic investigation of the discourse phenomena transmitted by the media. It is also an academic work that seeks to critically examine the phenomenon of speech, political speech, content analysis, of those appliances of social pressure which are operated through the media, transferring related narratives to systems of ideological reproduction. This article means a contribution to democratize contents of system analysis in social groups that contribute to promote common reflections to the world of language and its realities: How can a methodology of analysis of political discourse make a difference when you know the details of the operation of the social domain through the word and its discursive stereotypes?, a question that has been asked in several occasions, from different perspectives, in this article since the political discourse.